A novel signal self-enhancement photoelectrochemical immunosensor without addition of a sacrificial agent in solution based on Ag2S/CuS/α-Fe2O3 n–p–n heterostructure films. Issue 15 (28th January 2020) - Chen, Min; Wang, Cun; Meng, Hui; Mo, Fangjing; Fu, Yingzi
Abstract : A novel signal self-enhancement photoelectrochemical immuno-sensor has been developed based on the curing of sacrificial agent SO3 2− coated-Au NPs sensitizing Ag2 S/CuS/α-Fe2 O3 n–p–n hetero-structure films for the first time. Abstract : A novel signal self-enhancement photoelectrochemical immuno-sensor has been developed based on the curing of sacrificial agent SO3 2− coated-Au NPs sensitizing Ag2 S/CuS/α-Fe2 O3 n–p–n hetero-structure films for the first time. This strategy has acquired high sensitivity and low background without addition of a sacrificial agent in solution in the detection of prostate antigen.